2017
DOI: 10.32674/jis.v7i3.204
|View full text |Cite
|
Sign up to set email alerts
|

International Students' Views on Local Culture: Turkish Experience

Abstract: The number of international students in Turkey has steadily increased in recent years. As they come from different geographical locations, their successful adaptation to a medium-sized country in-between three continents is of great interest. This study was conducted to investigate international students’ perceptions of their Turkish experience. After an interview with 9 international students, a 46-item questionnaire was developed and given to 421 students; of these, 319 students from 61 countries returned co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Studies have suggested that Muslim students tend to choose a Muslim host country for their education (Çetin et al, 2017 ). Our research findings support this claim, as every student interviewed stated that one of the main reasons for choosing Türkiye was their religious concerns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that Muslim students tend to choose a Muslim host country for their education (Çetin et al, 2017 ). Our research findings support this claim, as every student interviewed stated that one of the main reasons for choosing Türkiye was their religious concerns.…”
Section: Resultsmentioning
confidence: 99%
“…According to McMahon ( 1992 ), the “push” or outbound model describes the disadvantageous factors of a home country that cause students to leave and study abroad, while the “pull” or inbound model describes the attractive qualities of the host country. The literature shows that for the Middle Eastern students, the pull factors to Türkiye are its geographical proximity to the Middle East and Europe (Türkiye being a passage to the latter), the supportive policies of the Turkish government toward Middle Eastern students and refugees (Aydin, 2021a ), the significant Muslim population in Türkiye (Çetin et al, 2017 ), and religious compatibility that positively influence student's decision to study abroad (Chang and Chou, 2021 ). In Addition, factors such as quality of education, affordability, recommendations from others, and scholarship opportunities (Ilhan et al, 2012 ; Özoglu et al, 2015 ; Snoubar, 2017 ; Aydin, 2021b ) are also found to be the pull factors for studying in Türkiye.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Same-sex hugging, kissing, or touching are rituals among Turks, expressing love, acceptance, and understanding (Mocan-Aydin, 2000). Besides, hugging close friends is a sign of solidarity among Turkish people, and Turks who regard hugging as normal tend to perceive more reserved people as being cold (Cetin et al, 2017). Sincerity and intimacy are therefore crucial factors in terms of emotional help seeking among TIS who are accustomed to Turkish norms and collectivistic relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The biggest adaptation problem for international students stems from cultural differences (Çetin et al, 2017;Gebru & Yuksel-Kaptanoglu, 2020). The difference between the society in which a person grew up and the culture he / she…”
Section: Cultural Adaptationmentioning
confidence: 99%